(untitled) (Bangladesh Journal of Botany, 2025)
A field experiment was performed at the forage research plot of Dr. Rajendra Prasad Central Agricultural University, Pusa, Bihar, India, during the winter season of 2022-23 to study the impact of different nitrogen levels and varieties on growth and fodder yield of maize varieties. The study was carried out in split plot design with three nitrogen levels in main plots (150, 180 and 210 kg/ha) and five maize varieties (NK 7550, NK 7328, NK 7660, J 1006 and Shaktiman-5) in sub plots with three replications. The results showed that J 1006 had the tallest plants (209.7 cm) and leaf : stem ratio (0.63); Shaktiman-5 had the widest internode diameter (38.3 mm) and J 1006 had the maximum total above-ground dry matter accumulation per plant (170.5 g). Regarding fodder yield, J 1006 surpassed other varieties, producing the highest green fodder yield (89.8 t/ha) and dry fodder yield (21.1 t/ha), except for NK 7660 and Shaktiman-5. Bangladesh J. Bot. 54(1): 159-166, 2025 (March)